Exploring the factors that influence the adoption of online pharmacy in Portugal: a study on consumer´s acceptance and pharmacist´s perception - Evelyn Livramento de Oliveira Santos (2021)
Due to the fast technological evolution and the penetration of the internet in people's daily lives, the online purchase of medicines and pharmaceutical products is an option that can bring several advantages to consumers' lives. Despite this, the adoption of this method by Portuguese consumers is still relatively low. Few studies have focused on the non-adopters' intention of use, and the pharmacist perception of online pharmacies in Portugal. Thus, this study aims to explore the factors that influence the adoption or non-adoption of this type of service, as well as to analyze the perspective of community pharmaceutical service providers. With this, this study also intends to design innovative improvement strategies for pharmaceutical e-commerce platforms. For this purpose, an online questionnaire was applied to Portuguese consumers regarding the awareness and practice of this method. An interview was also designed aimed at analyzing how pharmaceutical professionals perceive the use of e-commerce in this sector in Portugal, this second tool being considered complementary to the first. The results indicate that there is a relatively high percentage of Portuguese people aware of the practice of purchasing medicines/pharmaceutical products over the Internet. Despite this, most have never used this service as a means of purchasing this type of product. The reasons most mentioned by the smaller part of the sample that uses this method are home delivery, convenience, and competitive prices, which is in line with the literature. On the other hand, the reasons most mentioned by respondents who have never used this method are lack of knowledge of this type of service, pharmacy preference, lack of trust, and lack of advice on products and their use. The results of the interviews may indicate that Portuguese community pharmacists still have limited confidence in the online sale of pharmaceuticals, although favorable opinions are increasing. From these results, it was possible to conclude that it is necessary to implement more effective marketing strategies, adequate organizational structures, and well-defined logistics processes that allow speed and efficiency in transport and delivery.